Evaluation of Cervical Lymphadenopathy in Children: Is Epstein-Barr Virus Infection Predictable? - KEPENEKLİ KADAYİFCİ, EDA; YAKUT, NURHAYAT (GALENOS YAYINCILIK, 2021)
Aim: The aim of this study was to evaluate the paediatric patients with cervical lymphadenopathy (LAP) and to compare the clinical and laboratory features between Epstein-Barr virus (EBV) infections and the other aetiologies. Methods: We conducted a retrospective, single-center study of paediatric patients with cervical LAP from a tertiary care hospital in Turkey between October 2017 and March 2020. The medical records including demographic information, clinical features and laboratory results were collected from paediatric patients with cervical LAP Patients were divided into two groups according to whether the aetiology of LAP was EBV infection or the others. Clinical and laboratory findings were compared between the two groups. Results: A total of 175 patients included in the study. Nonspecific lymphadenitis was the most common diagnosis occurring at a rate of 54.3%. EBV infection was responsible for 17.1% of all causes. The presence of fever, white blood cell (WBC) and lymphocyte count were significantly higher and LAP size was significantly larger in patients with cervical LAP caused by EBV infection. Conclusion: Fever, elevated WBC and lymphocyte count may be predictors for EBV infection in children with cervical LAP. In patients who had these features, serological tests for EBV could make a significant contribution to reach an accurate diagnosis without wasting time.
Keywords: Cervical LAP children; EBV infection; PERIPHERAL LYMPHADENOPATHY; LABORATORY FINDINGS; CLINICAL-FEATURES; MANAGEMENT